2010
DOI: 10.1111/j.1440-172x.2010.01829.x
|View full text |Cite
|
Sign up to set email alerts
|

Workplace violence: Differences in perceptions of nursing work between those exposed and those not exposed: A cross‐sector analysis

Abstract: Acknowledgement:This and previous studies were funded by the Queensland Nurses" Union. We wish to thank all the members who responded to this survey for their participation. ABSTRACTNurses are at high risk of incurring workplace violence during their working life. This paper reports the findings on a cross sectional, descriptive, self-report, postal survey in 2007. A stratified random sample of 3,000 of the 29,789 members of the Queensland Nurses Union employed in the public, private and aged care sectors res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 37 publications
6
75
1
2
Order By: Relevance
“…[1][2][3][4] Unfortunately, however, workplace abuse directed at front line health professionals is a common problem in several countries, [5][6][7][8][9][10][11] including Australia. [12][13][14][15][16][17][18][19][20] A recent systematic review of studies of the prevalence of patient-initiated abuse perpetrated against Australian general practitioners found 12 month period prevalence ratios ranging from 48 to 64%. 15 Similarly, a large study of nurses who were practising in Tasmania found a 1 month period prevalence of 64%.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Unfortunately, however, workplace abuse directed at front line health professionals is a common problem in several countries, [5][6][7][8][9][10][11] including Australia. [12][13][14][15][16][17][18][19][20] A recent systematic review of studies of the prevalence of patient-initiated abuse perpetrated against Australian general practitioners found 12 month period prevalence ratios ranging from 48 to 64%. 15 Similarly, a large study of nurses who were practising in Tasmania found a 1 month period prevalence of 64%.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies from Australia (Roche et al 2010 andHegney et al 2010) reported the incidence of nurse to nurse bullying as ranging from 14.7% to 21.7% and studies in 4 the United States of America (USA) (Vessey et al 2009 andJohnston et al 2010) found rates of 23% and 27.3% respectively. Cahu et al (2014) surveyed 259 nurses in Brazil to investigate the incidence and experiences of what these researchers referred to as moral harassment.…”
Section: Incidence Of Bullyingmentioning
confidence: 99%
“…A convenience sample of nurses (n = 302, 86.4%) working in remote areas of Australia were concerned for their personal safety in relationship to work-related victimization [9] . Approximately 14% of a convenience sample of social workers working in the United Kingdom felt extremely vulnerable or very vulnerable to work-related victimization [10] ; whereas, Hegney, Tuckett, Parker, and Eley found that 57% of victimized Australian nurses from a stratified random sample did not consider their workplace adequately safe [11] . No published studies to date have offered a broad view or comparison of healthcare fields for perception of safety from work-related victimization.…”
Section: Work-related Victimizationmentioning
confidence: 99%